Unveiling the dual role of heterotrophic ammonia-oxidizing bacteria: enhancing plant regrowth through modulating cytokinin delivery - Wang, Xiao-Ling; Si, Zhen-Qiang; Yu, Hao; Qi, Lin; Liu, Wei; Shi, Jiang; Song, Peng (Frontiers in Microbiology, 2023)
This study aims to investigate the dual impacts of heterotrophic ammonia-oxidizing bacteria (HAOB) strains on the regrowth of Italian ryegrass by studying cytokinin delivery from roots to leaves. The dual impacts encompass both the "soil-inside-role" and "soil-outside-role," which refer to the HAOB operating inside and outside the rhizosphere soil within the rhizosphere microenvironment. The experimental design consisted of two sets of experiments, Exp-1 and Exp-2, involving different treatments. In Exp-1, various concentrations of NO 3 − were added to the roots to observe the soil-inside-role on cytokinin delivery from roots to leaves. In Exp-2, NO 3 − addition was combined with HAOB inoculation to observe the combined effects of the root-outside-role and root-inside-role on cytokinin synthesis and transport. The results indicated that NO 3 − concentrations ranging from 30 to 40 mmol•L −1 had the most optimal effect on increasing leaf cytokinin content and delivery from roots to leaves, consequently promoting greater leaf regrowth biomass. When inoculated, the HAOB strain significantly increased rhizosphere soil nitrification rates under the soil-inside-role, leading to increased NO 3 − release from the soil and a subsequent boost in cytokinin delivery from roots to leaves. Additionally, the HAOB strain independently enhanced cytokinin delivery from roots to leaves outside the rhizosphere soil within the rhizosphere microenvironment, demonstrating its soil-outside-role. The combined effects of the soil-inside-role and soil-outsiderole substantially increased leaf cytokinin content, playing a crucial role in promoting Italian ryegrass regrowth. The study's findings shed light on the mechanisms through which HAOB can enhance plant growth by performing dual roles in the rhizosphere, offering potential applications in agriculture. Understanding the interaction between HAOB, cytokinins, and plant growth could lead to more effective strategies for improving crop productivity and promoting sustainable agriculture.